Serology for brucellosis in free-ranging crab-eating foxes (Cerdocyon thous) and brown-nosed coatis (Nasua nasua) from Brazilian Pantanal - Dorneles, Elaine Maria Seles; Pellegrin, Aiesca Oliveira; Péres, Igor Alexandre Hany Fuzeta Schabib; Mathias, Luis Antônio; Mourão, Guilherme; Bianchi, Rita De Cassia; Olifiers, Natalie; Rocha, Fabiana Lopes; Lage, Andrey Pereira (Universidade Federal de Santa Maria, 2014)
A serological survey in free-ranging crab-eating foxes (Canidae: Cerdocyon thous) and brown-nosed coatis (Procyonidae: Nasua nasua) was performed in the Nhecolândia sub-region of the Brazilian Pantanal to evaluate the presence of anti-smooth Brucella antibodies on those wild populations. The detection of anti-smooth Brucella antibodies was performed by the Rose Bengal Test (RBT) as screening test and the Fluorescence Polarization Assay (FPA) as a confirmatory test. The frequency of smooth Brucella seropositive animals were 13.2% (5/38, 95% CI: 4.4% - 28.1%) for crab-eating foxes and 8.8% (3/34, 95% CI: 1.9% -23.7%) for brown-nosed coatis. No association was found between seropositivity for brucellosis and gender or age. The results of this study suggest exposure to or infection of crab-eating fox and brown-nosed coati from the Brazilian Pantanal by Brucella spp

Um inquérito sorológico em quatis (Procyonidae: Nasua nasua) e lobinhos (Canidae: Cerdocyon thous) de vida livre foi conduzido na sub-região da Nhecolândia do Pantanal Sulmatogrossense para avaliar a presença de anticorpos anti-Brucella (fenótipo liso). A pesquisa de anticorpos anti-Brucella foi realizada pelo teste do antígeno acidificado tamponado, utilizado como teste de triagem e pelo teste de polarização fluorescente, utilizado como teste confirmatório. A frequência de animais soropositivos para anticorpos anti-Brucella foi de 13,2% (5/38, IC 95%: 4,4% - 28,1%) para lobinhos e de 8,8% (3/34, IC 95%: 1,9% - 23,7%) para coatis. Não foi encontrada associação entre a soropositividade para brucelose e gênero ou idade. Os resultados deste estudo sugerem exposição a ou infecção de lobinhos e quatis do Pantanal Brasileiro por Brucella spp
Sorologia para brucelose em lobinhos (Cerdocyon thous) e coatis (Nasua nasua) de vida livre do Pantanal Brasileiro
Keywords: Brasil; Brucella; Pantanal; Cerdocyon thous; Nasua nasua; reservatórios; epidemiologia; Brazil; Brucella; Pantanal; Cerdocyon thous; Nasua nasua; reservoirs; epidemiology